Resilience framework for critical infrastructures: An empirical study in a nuclear plant. (September 2015) - Labaka, Leire; Hernantes, Josune; Sarriegi, Jose M.
Abstract: The safety and proper functioning of Critical Infrastructures (CIs) are essential for ensuring the welfare of society, which puts the issue of improving their resilience level at the forefront of the field of crisis management. Most of the resilience-building principles defined in the literature do not cover all the dimensions that make up resilience and most of them only focus within the boundaries of the CI, neglecting the role of the external agents that also have an influence on enhancing resilience. Furthermore, most of the principles that are present in the literature are theoretical and difficult to implement in practice. In light of this situation, the aim of this research is to present a holistic resilience framework for critical infrastructures in order to improve their resilience level by taking into account internal and external agents and covering all the resilience dimensions. Furthermore, this framework has been defined in close collaboration with the general management of CIs to facilitate its implementation in practice. Finally, in order to illustrate the value added of this framework it was implemented in a nuclear plant. Highlights: Resilience protects against foreseen and unpredicted events. There are two types of resilience: internal resilience and external resilience. Sixteen policies and thirty sub-policies assist on building resilience. Power nuclear plant focused on risk management approach rather than resilience. The plant's event driven risk management was enhanced with an all hazard approach.